A brief review on sustainable utilisation of marble waste in concrete. Issue 4 (3rd July 2020) - Kore, Sudarshan D.; Vyas, A. K.; Kabeer K.I., Syed Ahmed
ABSTRACT: A vast amount of non-biodegradable waste is generated during mining and processing operations of dimensional stones such as marble. This, over the years has become a global nuisance by damaging the environment through means of more than one. Therefore it has become necessary to find a technique to safely dispose or reuse marble waste. On the other hand, the construction industry is the one of the major consumers of natural resources for production of materials binders and aggregates. Hence in recent years, various researchers have conducted studies, where different types of marble waste have been incorporated in concrete with an aim of replacing cement or aggregates or both. This paper reviews such papers where dimensional stone waste produced from marble mining and processing is tested as a constituent of concrete. The impact of replacement of the conventional materials by marble waste was studied in terms of fresh, mechanical and durability properties of concrete. It can concluded that, use of marble powder as a 10% replacement of cement does not have any adverse impact on the properties of concrete or mortars. It is more beneficial when marble waste is combined with fly ash and then is used as a binder rather than just as a replacement of ordinary Portland Cement. On the other hand, replacement of fine and coarse aggregate by marble waste can be done between the range of 50% and 75%. The performance depends on the geological origin of the coarse aggregate and particle size distribution of the fine aggregate the waste is replacing.